2020
DOI: 10.1016/j.asmr.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Open Versus Arthroscopic Treatment of Chronic Lateral Epicondylitis and Worker’s Compensation

Abstract: Purpose: To compare the short-term outcomes between arthroscopic and open procedures for the treatment of lateral epicondylitis. Because a significant portion of patients have worker's compensation (WC), the outcomes in these subgroups were separately analyzed. Methods: A retrospective analysis of patients who had surgical treatment of lateral epicondylitis by a single surgeon from 2010 to 2017 was performed. Patients who were symptomatic after 9 months of conservative treatments including nonsteroidal medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 7 , 25 , 39 Other reported advantages of arthroscopic surgery include the improvement of symptoms, earlier return to work (RTW), and shorter recovery periods compared with open surgery. 4 , 13 , 32 However, it is evident that some patients still experience pain after arthroscopic debridement surgery. 4 , 14 , 21 Kwon et al 19 found that 2 patients (6.9%) still had poor outcomes after arthroscopic debridement treatment of chronic lateral elbow tendinopathy at a mean follow-up of >31 months.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 25 , 39 Other reported advantages of arthroscopic surgery include the improvement of symptoms, earlier return to work (RTW), and shorter recovery periods compared with open surgery. 4 , 13 , 32 However, it is evident that some patients still experience pain after arthroscopic debridement surgery. 4 , 14 , 21 Kwon et al 19 found that 2 patients (6.9%) still had poor outcomes after arthroscopic debridement treatment of chronic lateral elbow tendinopathy at a mean follow-up of >31 months.…”
mentioning
confidence: 99%
“… 4 , 13 , 32 However, it is evident that some patients still experience pain after arthroscopic debridement surgery. 4 , 14 , 21 Kwon et al 19 found that 2 patients (6.9%) still had poor outcomes after arthroscopic debridement treatment of chronic lateral elbow tendinopathy at a mean follow-up of >31 months. They proposed that arthroscopic debridement could not completely remove the tendinosis at the ECRB origin, as visualization of the full extent of the ECRB insertion at the lateral epicondyle was difficult using a 30° arthroscope.…”
mentioning
confidence: 99%